Culturally Adapted STAR-Caregivers Virtual Training and Follow-Up for Latino Caregivers of People Living With Dementia: Single-Arm Pre-Post Mixed Methods Study - Mariscal, Miguel Angel; Garcia, Celeste; Zavala, Lily; Ramirez, Magaly (JMIR aging, 2025)
Latino caregivers are at an increased risk of negative health outcomes due to the responsibilities of caring for someone with dementia. Although interventions exist to address caregiver burden, they often do not meet the cultural needs of Latino caregivers. This study aimed to pilot test the cultural adaptation of the STAR-Caregivers Virtual Training and Follow-Up (STAR-VTF) intervention. The intervention is an evidence-based training program designed to teach family caregivers strategies to manage behavioral and psychological symptoms of dementia (BPSD). Our research team has conducted past studies to identify and perform culturally relevant adaptations to the training modules of STAR-VTF, and this study aimed to pilot these culturally adapted modules with a sample of Latino caregivers. Data on feasibility, usability, and acceptability were collected from a pilot test in which Latino caregivers (n=16) used the training modules of the STAR-VTF intervention over a 7-week period. Participants completed usability surveys following the completion of each module, and acceptability was assessed through semistructured interviews (n=14) postintervention. Preliminary outcome measures were also collected, and a descriptive analysis was conducted. The primary outcomes were the Revised Memory and Behavior Problem Checklist (RMBPC) and the Preparedness for Caregiving Scale. The pilot study results suggest that it is feasible to deliver the culturally adapted STAR-VTF intervention to Latino caregivers, with 94% (15/16) of participants maintaining enrollment through intervention completion. The intervention's usability was found to be "good" based on an average System Usability Score of 76.7 out of 100 across all training modules. Caregivers were generally satisfied with the training modules. In addition, preliminary outcome results demonstrated a trend of decreased BPSD pre- versus postintervention (RMBPC subscale score: 28.24 to 21.34). Findings also demonstrated decreased caregiver reaction to BPSD pre- versus postintervention (RMBPC subscale score: 40.40 to 37.21) and increased caregiver preparedness based on pre- and postintervention (Preparedness Caregiving Scale score: 1.98 to 2.43). The pilot study demonstrated that the culturally adapted STAR-VTF intervention is feasible and perceived as easy to use by a small sample of Latino caregivers. We aim to refine the cultural adaptations of the STAR-VTF intervention further based on feedback from study participants. Future studies are necessary to test the efficacy of the intervention and support the broad dissemination of the culturally adapted intervention.